2013
DOI: 10.1159/000347217
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease in Prepubertal Children Born Small for Gestational Age: Influence of Rapid Weight Catch-Up Growth

Abstract: Background/Aims: We studied the association of low birth weight with ultrasound-assessed nonalcoholic fatty liver disease (NAFLD) to test the hypothesis that fetal growth retardation followed by a rapid weight catch-up growth might be an additional factor responsible for liver steatosis via insulin resistance (IR) and/or intra-abdominal fat. Methods: We enrolled 23 children born small for gestational age (SGA) with a rapid catch-up growth within the first 6-12 months, and 24 appropriate for gestational age (AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 45 publications
3
41
0
3
Order By: Relevance
“…Numerous studies have concluded that IUGR individuals, especially those with postnatal accelerated growth, are prone to develop insulin resistance and T2DM in adulthood (11)(12)(13). Using a well-established rodent model, these experiments have found that CG-IUGR rats had higher methylation level of specific CpG sites of PGC-1α promoter, in contrast, reduced PGC-1α transcription activity, mitochondrial content as well as protein level of key components of insulin-signaling pathway in liver and muscle tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have concluded that IUGR individuals, especially those with postnatal accelerated growth, are prone to develop insulin resistance and T2DM in adulthood (11)(12)(13). Using a well-established rodent model, these experiments have found that CG-IUGR rats had higher methylation level of specific CpG sites of PGC-1α promoter, in contrast, reduced PGC-1α transcription activity, mitochondrial content as well as protein level of key components of insulin-signaling pathway in liver and muscle tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Many intrauterine growth restriction (IUGR) infants experience postnatal accelerated growth (8), begetting shortterm (9) and long-term health benefits, especially in cognition and academic achievement (10). However, emerging evidence suggests that IUGR followed by postnatal accelerated growth (CG-IUGR) plays a role in the programing of adult metabolic disease risk (11)(12)(13), and the underlying molecular pathogenesis is unclear. Nevertheless, the epigenetic dysregulation has been implicated.…”
mentioning
confidence: 99%
“…Similarly, in our study, the link between SGA and liver damage was independent and in addition to insulin resistance, reflecting a more profound alteration possibly related the adverse intrauterine environment. Studies in adults and children born SGA indicate that insulin resistance is the earliest component associated with low birthweight, irrespective of confounding factors, including obesity and a family history of T2DM [37][38][39]. Nutrition in an adverse intrauterine environment during foetal life can be able to trigger a metabolic adaptation by epigenetic regulation of gene expression and thereby permanently sets functional capacity, metabolic competence, and responses to the later environment that favour NAFLD [40].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Nobili et al [41] have found in 90 Italian children an association between paediatric NAFLD with IUGR, independently of insulin resistance. Accordingly, Faienza et al [42] more recently have reported 34.8% of NAFLD out of 23 SGA children demonstrating that the insulin resistance index significantly correlates with liver steatosis at ultrasound.…”
Section: Role Of Intrauterine Environment In Nafld and Ms Cross-talkmentioning
confidence: 99%